The ore minerals under the microscope : an optical guide - Pracejus, Bernhard (Burlington : Elsevier Science, 2015)
The Ore Minerals Under the Microscope: An Optical Guide, Second Edition, is a very detailed color atlas for ore/opaque minerals (ore microscopy), with a main emphasis on name and synonyms, short descriptions, mineral groups, chemical compositions, information on major formation environments, optical data, reflection color/shade comparison with four common/standard minerals of a similar color or grey shade, and up to five high-quality photos for each mineral with scale. In addition, the atlas contains a compilation from some of the prominent publications in the field of ore microscopy prese.
Front Cover; The Ore Minerals Under the Microscope; Copyright; Table of Contents; Acknowledgements; Preface to the Second Edition; Explanations & Abbreviations; Textures; Magmatic Environments; Post-magmatic Environments; Post-magmatic Environments; Metamorphic Environments; Sedimentary Environments & Soils; Supergene Replacement; Biomineralisation; Optical Characteristics -- Search Index; Mineral Descriptions; I -- Elements; I/A -- Metallic and Intermetallic Compounds, Carbides, Nitrides, Phosphides, and Silicides; Copper, native I/A.01-010; Silver, native I/A.01-020; Gold, native I/A.01-040
Includes bibliographical references and index.
Print version record.
Keywords: Ores -- Atlases; NATURE -- Rocks & Minerals; SCIENCE -- Earth Sciences -- Mineralogy; Ores; Electronic books; Scientific atlases